Evidence and policy implications of climate-smart agriculture in Kenya - Chesterman, Sabrina; Neely, Constance (2015)
This technical paper details findings and outcomes from the workshop hosted by the Climate Change Unit of Ministry of Agriculture, Livestock and Fisheries of Kenya, along with the FAO, ICRAF and CCAFS. The process engaged stakeholders from research, practice and policy and to interactively share and analyze scientific evidence and field experience from over 40 projects related to climate-smart agriculture (CSA) within integrated farming systems in Kenya. A current state of knowledge on how CSA serves to simultaneously achieve Kenya’s development goals and climate change targets and relevant policy linkages is presented. Overarching recommendations for outscaling CSA in Kenya consider that: integration is required at all different levels;; access to productive inputs and markets is essential;; knowledge generation and sharing are critical for evidence based decision making;; inclusiveness and contextualisation promote ownership and uptake;; and the importance of building synergy and addressing potential inconsistencies between policies, regulations and implementation. Lastly, evidence-based and jointly agreed upon messaging regarding CSA is presented, as a contribution to the policy dialogues of the UNFCCC (COP 20, December, Peru[1]), Paris 2015 and other international efforts and fora, including the Alliance for CSA in Africa. The key policy recommendations elaborate upon: the consideration of development priorities;; connection of interdisciplinary research, practice and policy;; integration of farm and landscape systems;; inclusion of women and youth;; connection of policy and regulations and the filling of identified knowledge gaps.